Fe3O4@SiO2@CuZnAl‐O Catalysts for Conversion of Lignin in Supercritical Methanol. Issue 1 (9th February 2021) - Chen, J.; Hui, S.; Bao, G.; Luo, J.; Meng, Y.; Li, J.; Wang, A.; Liang, S.
Abstract: The catalytic degradation of lignin was exploited by magnetic core‐shell Fe3 O4 @SiO2 @CuZnAl‐O catalysts in supercritical methanol (sc‐MeOH) over temperature from 260 °C to 360 °C and the reaction time ranging from 0.5 h to 5 h. The magnetic core‐shell‐structured Fe3 O4 @SiO2 @CuZnAl‐O catalysts with different mole ratio of Cu to Zn were prepared by parallel flow co‐precipitating method. Catalyst Fe3 O4 @SiO2 @Cu1.2 Zn4.8 Al2 ‐O with the maximum specific surface area (142.8 m 2  g −1 ) exhibited the highest lignin conversion of 66% and high selectivity for phenols, ketones and benzenes. The recyclable Fe3 O4 @SiO2 @CuZnAl‐O catalyst allows high catalytic activity and selectivity for phenols, ketones and benzenes in the catalytic conversion of lignin in supercritical methanol. It is believed that this study can provide a promising strategy to prepare core–shell structured base metal nanocatalysts with metal‐oxide shells.